2021
DOI: 10.1186/s13063-021-05717-4
|View full text |Cite
|
Sign up to set email alerts
|

PRagMatic Pediatric Trial of Balanced vs nOrmaL Saline FlUid in Sepsis: study protocol for the PRoMPT BOLUS randomized interventional trial

Abstract: Background/aims Despite evidence that preferential use of balanced/buffered fluids may improve outcomes compared with chloride-rich 0.9% saline, saline remains the most commonly used fluid for children with septic shock. We aim to determine if resuscitation with balanced/buffered fluids as part of usual care will improve outcomes, in part through reduced kidney injury and without an increase in adverse effects, compared to 0.9% saline for children with septic shock. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
(57 reference statements)
0
12
0
2
Order By: Relevance
“…Besides, it is unrealistic to set a 100% complete grouping solution. So we de ne a well adherence as receipt of ≥80% of total randomly assigned solution referenced to a paediatric sepsis study [29]. Our study aims to nd a predominant balanced crystalloid uid better than normal saline used in SAP for supplemental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is unrealistic to set a 100% complete grouping solution. So we de ne a well adherence as receipt of ≥80% of total randomly assigned solution referenced to a paediatric sepsis study [29]. Our study aims to nd a predominant balanced crystalloid uid better than normal saline used in SAP for supplemental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent observational study of 99 pediatric sepsis found a decrease in acute kidney injury, need for renal replacement therapy and hospital length of stay with balanced crystalloids [ 48 ]. Thus, the debate is not over and the results of an ongoing international RCT with anticipated enrollment of 8,800 children with septic shock are eagerly awaited [ 49 ], especially as two recent large RCTs in adults ICUs did not report improved survival with balanced crystalloids [ 50 , 51 ].…”
Section: Rationalementioning
confidence: 99%
“…8 Thus, it remains to be seen if balanced solutions are superior to NS in pediatric intensive care settings. 9 A large portion of the documented pediatric dysnatermia cases is iatrogenic and related to fluid composition. 10 Consequently, it is not unreasonable to assume that the amount of fluid given is equally important as the choice of fluid.…”
Section: E D I T O R I a L Dysnatremia In Children Why Is It So Hard ...mentioning
confidence: 99%